Giuseppe's Italian bakes : over 60 classic cakes, desserts & savoury bakes - Dell'Anno, Giuseppe (Quadrille Publishing, 2022)
"Giuseppe Dell'Anno won hearts the world over when he was crowned winner of the Great British Baking Show in 2021. In Giuseppe's Italian Bakes, his first cookbook, Giuseppe shares his skill, knowledge and love of baking through over 60 new sweet and savory recipes. Growing up in Italy and learning to cook at the side of his beloved chef-father, Giuseppe has mastered everything from focaccia to florentines, each with his own signature twist on the classics of Italian baking. Through his step-by-step recipes, Giuseppe guides you through making focaccia, pannacotta, tiramisù, rum baba, piadine, Sicilian cannoli and, of course, pizza, among many other delectable treats. With gorgeous color photos throughout and tips and tricks from the master of the technical challenge, bring a taste of the Italian bakery to your home with Giuseppe's Italian Bakes"--